EFEKTIVITAS PENGGUNAAN RADAR ARPA GUNA MENGHINDARI TUB-RUKANN DI KMP. WIRA BERLIAN - Aida Restu Hidayah; Rizal Rochmansyah; Arya Widiatmaja; Melda Yanti; Kurniawan Abadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Shipping is an integral part of the national maritime transportation system and serves as a vital means of supporting the achievement of national development goals. According to the International Maritime Organization (IMO) 2019, passenger ships—including Roll-on/Roll-off (Ro-Ro) passenger ships—are required to utilize all available navigation aids, such as radar and ARPA, to conduct effective surveillance and assess the risk of collision. This study employs a descriptive qualitative method, with informants selected through purposive sampling, namely the Captain, First Mate, Second Mate, Third Mate, and Helmsman. Data were collected through interviews, observations, and documentation using interview and observation checklists. Data analysis was conducted through data reduction, fishbone diagrams, data presentation, and drawing conclusions. The results of the study indicate that the effectiveness of Radar and ARPA usage on the KMP. Wira Berlian is influenced by human, methodological, equipment, measurement, and environmental factors, including the vigilance of the officer on watch, radar configuration procedures, component condition, CPA/TCPA monitoring, as well as weather and vessel traffic density